Essential oil and fatty acid composition of Melissa officinalis L. - Souihi, Mouna; Amri, Ismail; Souissi, Amir; Hosni, Karim; Ben Brahim, Nadia; Annabi, Mohamed (Progress in Nutrition, 2020)
The leaf material of lemon balm (Melissa officinalis L.) from different origins was evaluated for their chemical composition under the semi arid conditions of Tunisia. Qualitative and quantitative variations of the chemical composition of essential oils according to the origin were shown. The main compounds of Tunisian samples were germacrene-D (29.17-24.6%) and caryophyllene (14.91-13.44%) in Tabarka and Nefza, the samples were characterized by the absence of citral and citronellal. Fatty acids from cultivated M. officinalis leaves were analyzed by GC–MS. The major fatty acids of all studied samples were polyunsaturated fatty acids, linoleic acid (73.93-66.74%), versus (16.25-13.32%) saturated ones, oleic acid and (6.29-4.26%) of monounsaturated fatty acid palmitic acid.